2003
DOI: 10.1097/00003246-200301000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in vitro hemodilution with hydroxyethyl starch and dextran on the activity of plasma clotting factors

Abstract: Both NaCl and Ringer solution cause measurable effects on coagulation factors at 10:4 hemodilution that can be explained by hemodilution alone. The effects on clotting factors of 10:4 hemodilution with HAES and Oncovertin were not significant. Even at 10:10 hemodilution with HAES or Oncovertin, the reduction in factor activities, although significantly (p <.04) different from baseline, was less than what was expected by dilution alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…Measuring with activated thrombeleastography and markedly shortened measuring time was, however, not able to confirm this phenomenon [37,38]. Moreover, Petroianu et al [39] concluded that hemodilution with crystalloids and colloids caused a decrease in the activity of various clotting factors in vitro. Thus, why hemodilution should activate coagulation while activated coagulation markers remain unchanged and the activity of various coagulation factors and the thrombocyte count decrease, is not known.…”
Section: Volume Therapy and Its Effect On Coagulationmentioning
confidence: 96%
“…Measuring with activated thrombeleastography and markedly shortened measuring time was, however, not able to confirm this phenomenon [37,38]. Moreover, Petroianu et al [39] concluded that hemodilution with crystalloids and colloids caused a decrease in the activity of various clotting factors in vitro. Thus, why hemodilution should activate coagulation while activated coagulation markers remain unchanged and the activity of various coagulation factors and the thrombocyte count decrease, is not known.…”
Section: Volume Therapy and Its Effect On Coagulationmentioning
confidence: 96%
“…The hemostatic consequences of hydroxyethyl starch (HES) administration have been intensely investigated in vitro [1][2][3][4][5][6][7][8][9] and in vivo [4, 10 -15]. In particular, administration of high molecular weight HES has been associated with increased post-operative hemorrhage after cardiopulmonary bypass [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, administration of high molecular weight HES has been associated with increased post-operative hemorrhage after cardiopulmonary bypass [16,17]. A universal finding has been that dilution in vitro or administration in vivo with high molecular weight HES with a large degree of substitution (DS) of hydroxyethyl groups per glucose unit is associated with a decrease in ex vivo measures of coagulation such as activated partial thromboplastin time [9,10,14], prothrombin time [5,9,10,13,14], or via thrombelastographic parameters [1-8, 10 -12, 14, 15]. With regard to thrombelastographic variables, the diagnosis of hypocoagulability can be made based on an increase in the time to clot initiation (prolonged reaction time, R), a decrease in the speed of clot propagation (decreased angle, ␣), or a decrease in clot strength (smaller amplitude, A; or shear elastic modulus, G).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations